Diagnostic challenges in clinical, radiological and histopathological tests regarding papillomatous lesions of the breast. (August 2018) - Rasmussen, Birgitte Bruun; Balslev, Eva; Jarle Christensen, Ib; Lanng, Charlotte; Bak, Anne; Galatius, Hanne; Møller Talman, Maj-Lis; Sharghi Someh, Nahid; Vejborg, Ilse; Okholm, Mette
Abstract: Papillomas of the female breast is a relatively frequent lesion, and the majority are benign when excised. However, some may host malignant or premalignant areas. Consequently, it is a worldwide accepted principle to excise the lesion whenever diagnosed. However, this leads to a large number of patients having an unnecessary operation. The present study was designed to investigate whether we could find clinical, radiological and pathological factors in the preoperative, diagnostic setting that could identify patients hosting a benign papilloma in order to avoid operation. The patient material consisted of 260 patients, all with a preoperative diagnosis of a papillomatous process in core biopsy. The lesion was excised, and 71% had a benign lesion. The rest had lesions ranging from premalignant to malignant. In the clinical, radiological and histopathological investigations conducted, we were not able to identify factors that statistically significant could predict whether the lesion was benign or malignant. However, our data showed a higher prevalence of malignant and premalignant lesions for older patient, larger lesions, and lesions found at a longer distance from the papilla. We conclude that, since almost 30% of the patients in our study ended up with a premalignant or malignant diagnosis, where no statistically significant preoperative factors could indicate a benign outcome, operation is warranted in all patients with a preoperative diagnosis of a papillomatous lesion. Highlights: In papillary tumors there are significant relation between old age, size and localization, and the risk of malignancy. No preoperative parameters can predict a benign papillary lesion on excision. Excision is needed in all cases of a core biopsy.